Effectiveness of Village Administration Coaching in Tompaso District Minahasa Regency - Onibala, Vino Satria; Kairupan, Sisca Beatrix; Bulo, Laurens (Technium Social Sciences Journal, 2024)
The main objective of this research is to analyze the effectiveness of village administration coaching in Tompaso District Minahasa Regency. This research uses a descriptive qualitative approach with primary data sources obtained through structured interview techniques to the sub-district head, sub-district secretary, village head, village secretary, government head in Tember, Kamanga, kamanga one, Sendangan, Liba, Tempok Selatan, Tempok, Talikuran, Tolok and Tolok one villages. Secondary data in the form of regulations, organizational structures and administrative activities of the sub-district head and Village General Administration book documents consisting of: 1) village regulation book, 2) Village head decision book, 3) Village inventory and wealth book, 4) Government apparatus book, 5) cash land book in the village, 6) land book in the village, 7) agenda book, 8) expedition book, and 9) village sheet book and village news. The results showed that the development of village government administration in Tompaso District Minahasa Regency has not been running effectively. This is because the administrative order has not been maximized, the village apparatus lacks discipline, and there is still a lack of socialization, limited technical guidance, weak supervision, and no incentives. For this reason, it is recommended: 1) that the village apparatus be given reinforcement in the form of socialization, technical guidance, and inherent supervision, 2) In order for the village apparatus to increase discipline in carrying out their duties and responsibilities, it is better to make a village head regulation to the village apparatus.